1984
DOI: 10.1016/s0007-0971(84)80091-1
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative lung scintigrams and lung function in the selection of patients for pneumonectomy

Abstract: A method for predicting postoperative respiratory function following lung resection has been used in 11 patients with both histologically proven bronchial carcinoma and chronic obstructive airways disease, in order to assess their fitness for surgical treatment. Quantitative ventilation and perfusion scintigrams were used to measure the amount of functioning tissue in each lung. These data were used in conjunction with spirometric measurements to calculate the likely functional effect of pneumonectomy. There w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

1987
1987
2010
2010

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 0 publications
0
5
0
Order By: Relevance
“…The reported correlation between the actual and predicted post-operative FEV1 using quantitative ventilation/perfusion scintigraphy has been variable, with correlative figures quoted between r50.67 to r50.9 [62,63,91,93,[95][96][97][98][99]. Either ventilation scintigraphy [99] or perfusion scintigraphy [62,63,91] offer good prediction of post-operative lung function, but there seems to be no additional benefit in performing both [99].…”
Section: Statementmentioning
confidence: 99%
See 1 more Smart Citation
“…The reported correlation between the actual and predicted post-operative FEV1 using quantitative ventilation/perfusion scintigraphy has been variable, with correlative figures quoted between r50.67 to r50.9 [62,63,91,93,[95][96][97][98][99]. Either ventilation scintigraphy [99] or perfusion scintigraphy [62,63,91] offer good prediction of post-operative lung function, but there seems to be no additional benefit in performing both [99].…”
Section: Statementmentioning
confidence: 99%
“…Either ventilation scintigraphy [99] or perfusion scintigraphy [62,63,91] offer good prediction of post-operative lung function, but there seems to be no additional benefit in performing both [99]. The interpretation of the results, however, needs to take into account the fact that these techniques may underestimate the actual post-operative value [63,93,98].…”
Section: Statementmentioning
confidence: 99%
“…[2−], 128 [2−], 129 [3], 130 [2−] There is also considerable uncertainty about the accuracy of quantitative perfusion to predict the postoperative FEV 1 in patients undergoing pneumonectomy 127. [2−], 129 [3], 131 [2−], 132 [3], 133 [3], 134 [3], 135 [3], 136 [2+] However, scintigraphy can be especially useful where an assessment has suggested that any further loss of lung function would be unacceptable if it is shown that no further (or minimal) lung function would be lost by operating. This applies where there may be compression of a pulmonary artery or marked emphysema in the lobe containing cancer.…”
Section: Section 2: Surgerymentioning
confidence: 99%
“…[2+] It is important to bear in mind that scintigraphy results may underestimate actual postoperative values 127. [2−], 131 [2−], 134 [3] …”
Section: Section 2: Surgerymentioning
confidence: 99%
“…In the comparison of estimated and measured postoperative functional values previous authors6-9 23 have generally quoted only the correlation coefficient, which in this context is inadequate18 as it fails to give an estimate of the accuracy of the predicted value. In the present series of 28 patients we have plotted 95% confidence limits and confirmed that the method is sufficiently accurate to be of clinical value.…”
Section: Scansmentioning
confidence: 99%